2022
DOI: 10.1002/gps.5833
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of late‐onset versus early‐onset bipolar disorder in a global sample of older adults

Abstract: Objectives Late‐onset bipolar disorder (LOBD) represents a significant subgroup of bipolar disorder (BD). However, knowledge for this group is mostly extrapolated from small studies in subjects with early/mixed age of illness onset. In this global sample of older adults with BD (OABD: ≥50 years old) we aim to characterize the sociodemographic and clinical presentation of LOBD (≥40 years at BD onset) compared to early‐onset BD (EOBD: <40 years at BD onset). Methods The Global Aging and Geriatric Experiments in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In a separate GAGE-BD study by our group, our group specifically looked at early onset BD (EABD) versus late onset BD (LOBD) in OABD/OOABD. 32 The results showed similar outcomes between LOBD and EOBD in severity of depression, mania, or functioning as well as prevalence of comorbidities except elevated risk of cardiovascular disease in LOBD. Therefore, it is less likely that differences in age of onset are driving the different…”
Section: Physical Comorbiditymentioning
confidence: 59%
See 1 more Smart Citation
“…In a separate GAGE-BD study by our group, our group specifically looked at early onset BD (EABD) versus late onset BD (LOBD) in OABD/OOABD. 32 The results showed similar outcomes between LOBD and EOBD in severity of depression, mania, or functioning as well as prevalence of comorbidities except elevated risk of cardiovascular disease in LOBD. Therefore, it is less likely that differences in age of onset are driving the different…”
Section: Physical Comorbiditymentioning
confidence: 59%
“…On the other hand, the better psychiatric outcomes of the OOABD and OABD might be a “cohort effect.” It is possible that these 3 groups of patients might represent 3 different cohorts of patients and each group had its own trajectory, that is, patients with late onset BD have a better outcome. In a separate GAGE‐BD study by our group, our group specifically looked at early onset BD (EABD) versus late onset BD (LOBD) in OABD/OOABD 32 . The results showed similar outcomes between LOBD and EOBD in severity of depression, mania, or functioning as well as prevalence of comorbidities except elevated risk of cardiovascular disease in LOBD.…”
Section: Discussionmentioning
confidence: 99%
“…There are several cut-off BD onset ages in the literature. For example, forty years old is a cut-off for early-onset and late-onset bipolar disorder (EOBD and LOBD) [26]. Approximately 30-60% of BD patients experience onset between ages 15 and 19, called pediatric or juvenile BD [27,28].…”
Section: Study Populationmentioning
confidence: 99%
“…Regarding age of onset, the GAGE-BD project compared EOBD and LOBD patients [ 23 ▪ ]. The authors reported that EOBD patients were not different in terms of severity of depressive and manic symptoms and functioning than LOBD patients.…”
Section: Diagnosis and Specifiersmentioning
confidence: 99%